The Study on the Challenges and Prospect on Marketing Nigeria Made Computer Software: A Case Study of Gombe Metropolis (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study examines the challenges and prospects of marketing Made-in-Nigeria software, with a focus on the Gombe State region. It investigates attitudes towards locally produced software, identifies societal problems affecting software marketing, analyzes challenges faced by software development students, explores factors influencing the preference for foreign software, and proposes strategies for promoting Made-in-Gombe software. The research questions address various aspects of software marketing and the behavior of Gombe consumers. The study finds that there are significant challenges in marketing Made-in-Gombe software, including perceived inadequate skills among developers, limited government support, and socioeconomic factors impacting students' software development, poor classroom environments, frequent lecturer transfers, and insufficient learning materials. Locally made software is also perceived as inefficient, and the high cost of hosting websites and deploying software hinders its development. The study's significance lies in aiding multinational and indigenous companies in Nigeria with effective marketing planning, providing insights for academics and marketing consultants, and encouraging further research in promoting Gombe-made products. While the study focuses on Gombe-made software, its findings can be applicable to other locally manufactured products. Recommendations are provided to address the identified challenges and improve the marketing of Made-in-Gombe software.